Diversity of secondary woody species in relation to species richness and cover of dominant trees in thermophilous deciduous forests. Issue 5 (3rd July 2016) - Carrari, Elisa; Ampoorter, Evy; Coppi, Andrea; Selvi, Federico
ABSTRACT: One of the prominent compositional features of thermophilous deciduous forests of southern Europe is their richness in secondary woody species (AWS). To date, no studies have focused on the diversity and contribution to the ecosystem functions and socio-economic benefits provided by these species. Here, we first characterized species richness and diversity for three main functional groups of AWS, sporadic trees, shrubs and vines, in 53 representative stands of central Italy. Secondly, we explored variations in AWS diversity and composition along a four-level gradient of species richness of dominant trees under comparable site conditions. The 40 AWS taxa recorded showed a remarkable taxonomic singularity at both the genus and the family rank. Dominant tree species richness had no significant effect on AWS species richness and composition, while Shannon diversity of AWS, especially shrubs, was associated with cover of the dominant trees. Each AWS possessed, on average, ca. five ability traits over a total of 13 considered that contributed to important ecosystem functions or expected socio-economic benefits such as wood and food production, conservation of genetic resources (wild crop relatives) and ornamentals. This highlights the key role of AWS, and in particular of sporadic trees, for enhancing multifunctionality of thermophilous deciduous forests.